A confecção de jogos matemáticos no ensino-aprendizagem nos anos iniciais do ensino fundamental - Suganuma, Agnes Sayori Yamashita (2023)
This work proposes to talk about the use of mathematical games in the Early Years of Elementary School in the teaching and learning process. The objectives are to propose a dynamic, motivating class, in which the student can learn by developing their own game and understanding abstract issues in a concrete way. Children in the Early Years Elementary School age group are transitioning from playful learning with games to literacy, therefore, they still need concrete objects for a better understanding and development of their cognitive skills. Developing skills, motor coordination, group relationships and their rules, creativity and playfulness. There are many challenges in teaching and learning Mathematics, therefore, proposing which methodologies and processes will influence the academic lives of both students and educators. Education is built throughout life and during this process, the educators who are involved together with the pedagogical team are part of this process that will form critical, responsible citizens who will perpetuate a fair Society in constant evolution.